Dinamika Persaingan Kopi Robusta Indonesia dengan Negara-Negara Pesaing Utama - Nia Rosiana; Rita Nurmalina; Ratna Winandi; Amzul Rifin (Jurnal Tanaman Industri dan Penyegar, 2018)
Fluctuations in Indonesian Robusta coffee exports occurred along with a declining trend in coffee exports compared to major competitor countries over the past fifteen years.  This research aimed to analyze the dynamics of the competitiveness of Indonesian Robusta coffee exports and the level of competition among the major competitor countries such as Vietnam and India. The methods used are Revealed Comparative Advantage (RCA), Dynamic Revealed Comparative Advantage (DRCA), and Rank Spearman Correlation. These methods were selected to analyze changes in competition level within 15 years’ time dimension (2000–2015) as well as to analyze the relationships among competing countries, which may affect Robusta coffee market of each country. The analysis showed that Indonesia's coffee competitiveness tends to increase compared to the two major competitors of Robusta coffee exporter of the world such as Vietnam and India. However, Indonesia's coffee competitiveness is still a half below Vietnam. The Indonesian coffee rivalry against Vietnam and India is not significantly correlated due to the different markets of export destination countries.  Increasing competitiveness and the strength of competition in export market can be done through quality improvement and continuity of domestic Robusta coffee in accordance to the demand of world consumers.